Ear-marking relief: a meta-analysis on the efficacy of Auricular Acupressure in alleviating anxiety disorders - Hu, Niaona; Soh, Kim Lam; Japar, Salimah; Li, Ting (S. Karger AG, 2024)
Background: The increasing worldwide mental health crisis, notably anxiety, emphasizes the urgency for available and effective interventions. Traditional therapies, although beneficial, pose limitations due to their considerable costs and possible adverse effects, thereby inviting alternative treatments such as auricular acupressure (AA). This non-pharmacological, integrative method, underpinned by Eastern and Western medical principles, presents a significant prospect for managing anxiety. Objective: This study aims to evaluate the existing evidence on the efficacy of AA in reducing anxiety, as elucidated through a systematic review. Methods: A comprehensive search of randomized controlled trials was conducted across various databases: the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, EMBASE, Web of Science, Chinese National Knowledge Infrastructure (CNKI), China Biology Medicine (CBM), Wan Fang, and Database for Chinese Technical Periodicals (VIP). Two reviewers retrieved the pertinent studies and assessed their methodological quality. A meta-analysis was then conducted, incorporating data from all relevant time points. Results: Upon examining 25 studies encompassing 1,909 participants, it was discerned that AA significantly diminished anxiety (SMD = −1.1074; 95% confidence interval, −1.348 to −0.801; z = 7.70, p < 0.01). Subgroup analyses indicated that neither an increased number of auricular points nor extended intervention augmented effects. Larger effect sizes were associated with probing and avoidance of sham acupressure. Notably, 23 of the 25 studies exhibited some bias, suggesting further research is necessary. Conclusions: The extant evidence advocates for AA as an effective supplementary intervention that reduces patient anxiety. The results hint at a potential placebo effect elicited by sham acupressure, necessitating rigorous control group definitions in future inquiries. The study findings suggest that fewer acupressure points and shorter intervention durations could effectively alleviate anxiety symptoms. Nonetheless, the significant heterogeneity across the studies underscores the requirement for more stringent research methodologies to substantiate these conclusions.